Characteristics of practitioners in a private managed behavioral health plan - Reif Sharon; Torres Maria E; Horgan Constance M; Merrick Elizabeth L (BMC, 2012)
Abstract Background Little is known about the practitioners in managed behavioral healthcare organization (MBHO) networks who are treating mental and substance use disorders among privately insured patients in the United States. It is likely that the role of the private sector in treating behavioral health will increase due to the recent implementation of federal parity legislation and the inclusion of behavioral health as a required service in the insurance exchange plans created under healthcare reform. Further, the healthcare reform legislation has highlighted the need to ensure a qualified workforce in order to improve access to quality healthcare, and provides an additional focus on the behavioral health workforce. To expand understanding of treatment of mental and substance use disorders among privately insured patients, this study examines practitioner types, experience, specialized expertise, and demographics of in-network practitioners providing outpatient care in one large national MBHO. Methods Descriptive analyses used 2004 practitioner credentialing and other administrative data for one MBHO. The sample included 28,897 practitioners who submitted at least one outpatient claim in 2004. Chi-square and t-tests were used to compare findings across types of practitioners. Results About half of practitioners were female, 12% were bilingual, and mean age was 53, with significant variation by practitioner type. On average, practitioners report 15.3 years of experience (SD = 9.4), also with significant variation by practitioner type. Many practitioners reported specialized expertise, with about 40% reporting expertise for treating children and about 60% for treating adolescents. Conclusions Overall, these results based on self-report indicate that the practitioner network in this large MBHO is experienced and has specialized training, but echo concerns about the aging of this workforce. These data should provide us with a baseline of practitioner characteristics as we enter an era that anticipates great change in the behavioral health workforce.